Increasing the technical effect of the outer wall insulation from foam concrete - Tuiakova Бану (Рroblems of engineering and professional education, 2023)
The article provides for thermal performance in exterior walls of houses at the moment are, to identify shortcomings in the future to improve thermal performance of exterior walls by insulating materials. As well as comparing the actual, technical and economic calculations, will offer the most effective option of insulation. For comparison, the following insulating materials: mineral wool slab, polystyrene, PIR panel.